2011
DOI: 10.1088/0004-637x/743/2/156
|View full text |Cite
|
Sign up to set email alerts
|

Neowise Observations of Near-Earth Objects: Preliminary Results

Abstract: With the NEOWISE portion of the Wide-field Infrared Survey Explorer (WISE) project, we have carried out a highly uniform survey of the near-Earth object (NEO) population at thermal infrared wavelengths ranging from 3 to 22 µm, allowing us to refine estimates of their numbers, sizes, and albedos. The NEOWISE survey detected NEOs the same way whether they were previously known or not, subject to the availability of ground-based follow-up observations, resulting in the discovery of more than 130 new NEOs. The sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
312
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(339 citation statements)
references
References 54 publications
(56 reference statements)
21
312
1
1
Order By: Relevance
“…Since the fitted beaming parameter values correlate with the phase angle of the observation, α (Delbo' et al 2003;Wolters & Green 2009), it is customary to use a default value (η d ) based on the average of particular asteroid populations whenever it is not possible to fit it (two or more thermal bands are required to have the necessary degree of freedom). An average value of 1.4 was found for NEAs (Mainzer et al 2011a), 1.2 for Mars-crossing asteroids (Alí-Lagoa & Delbo' 2017), 1.0 for MBAs (Masiero et al 2011), and 0.77 for Hildas and Jupiter Trojans ). Here we considered our sample's statistics to choose a default value of η as a function of α.…”
Section: Thermal Modellingmentioning
confidence: 95%
See 2 more Smart Citations
“…Since the fitted beaming parameter values correlate with the phase angle of the observation, α (Delbo' et al 2003;Wolters & Green 2009), it is customary to use a default value (η d ) based on the average of particular asteroid populations whenever it is not possible to fit it (two or more thermal bands are required to have the necessary degree of freedom). An average value of 1.4 was found for NEAs (Mainzer et al 2011a), 1.2 for Mars-crossing asteroids (Alí-Lagoa & Delbo' 2017), 1.0 for MBAs (Masiero et al 2011), and 0.77 for Hildas and Jupiter Trojans ). Here we considered our sample's statistics to choose a default value of η as a function of α.…”
Section: Thermal Modellingmentioning
confidence: 95%
“…This technique, called radiometry, has been the major contributor of asteroid diameters since the 1980s, when the Infrared Astronomical Satellite (IRAS) allowed two thousand asteroid diameters to be determined (Tedesco 1986;Tedesco et al 2002b). After a modest addition of observations of approximately 150 more asteroids by the Midcourse Space Experiment (MSX) in the 1990s (Tedesco et al 2002a), there has been two major space-based all-sky surveys at thermal infrared wavelengths in the last ten years: AKARI (Murakami et al 2007) and WISE/NEOWISE (Wright et al 2010;Mainzer et al 2011a). Usui et al (2011), henceforth U11, used the 9-and 18-µm AKARI all-sky fluxes to produce the Asteroid catalogue using AKARI (AcuA), comprising 5000 asteroid diameters and visible geometric albedos based on an empirical calibration of the standard thermal model (STM) (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal inertia of 1950 DA was determined using archival WISE thermal-infrared observations, which were obtained on 12-13 July 2010 UT during the WISE All-Sky survey 15 were taken, and was only detected at 3-σ levels or greater in the W3 (11 μm) and W4 (22 μm) channels. Additionally, we only used data points that repeatedly sampled common rotation phases of 1950 DA to ensure consistency, and to avoid outliers, within the data set.…”
Section: Analysis Of Wise Thermal-infrared Observationsmentioning
confidence: 99%
“…Initially limited in number by practical constraints on ground-based observations, thermal observations of Herschel is an ESA space observatory with science instruments provided by European-led Principal Investigator consortia and with important participation from NASA. Table 3 is available in electronic form at http://www.aanda.org asteroids have quickly expanded to large surveys, such as IRAS in 1983 (2200 objects in 1983, Tedesco et al 2002), AKARI in 2006-2007 (about 5000 objects, Usui et al 2013), Warm Spitzer ExploreNEO since 2009 (600 near-Earth objects, Trilling et al 2012), and WISE/NEOWISE in 2009-2010, which observed over 150 000 small bodies at 3.4, 4.6, 12, and 22 μm, including some 100 000 main-belt asteroids (Masiero et al 2011), over 400 NEOs (Mainzer et al 2011a), and about 2000 Trojans ).…”
Section: Introductionmentioning
confidence: 99%